The Effect of Intrinsic Motivation and Religiosity to Social Media Awareness around 'Fodamara Tv' Youtube Team - Nurfauzy Lubis; Rubino Rubino; Nur Hanifah (JURNAL AT-TURAS, 2022)
One of the youth mosque communities that are moving to become virtual preachers is Forum Pemuda Masjid Raya (Fodamara) Senapelan, Pekanbaru. They started their da'wah activism on social media through the "Fodamara TV" Youtube channel. This study aims to determine whether there is an effect between intrinsic motivation and religiosity to awareness of social media da'wah among the youtube team 'Fodamara TV'. This research is a quantitative descriptive using a census sampling technique in which the entire population is used as a sample of 35 people. The results of the multiple regression test show that the variables X1 and X2 are equally influential and correlated to the Y variable with a value contribution of 85.4%. In addition, the magnitude of the influence between intrinsic motivation and religiosity (simultaneously) on awareness of preaching has a significant effect of 0.636. Also, the religiosity variable has a significant effect of 0.467 on awareness of preaching.